Analysis of Teachers’ Readiness toward the School Literacy Movement at the Learning Stage ini Elementary School - Izza Desmita; Otang Kurniaman; Eddy Noviana (Jurnal Pembelajaran Bahasa dan Sastra, 2026)
This study is grounded in the importance of the teacher’s role in integrating literacy into the learning process through the Learning Stage of the School Literacy Movement (Gerakan Literasi Sekolah/GLS) in elementary schools. The study aims to describe the level of teachers’ readiness to implement GLS at the learning stage based on demographic variables, namely gender, educational level, length of teaching experience, and certification status. A descriptive quantitative approach was employed, involving 180 teachers from 11 elementary schools in the Lancang Kuning Cluster, selected using proportional random sampling. The research instrument was a Likert-scale questionnaire consisting of 42 statements that had been tested and proven valid (r > 0.312) and reliable (Cronbach’s Alpha = 0.987). The results indicate that overall teacher readiness falls within the high category, with mean scores ranging from 3.72 to 3.96. Demographic analysis also shows consistent results. Female teachers have a mean score of 3.82, while male teachers score 3.56. Teachers holding a master’s degree (S2) show the highest mean score of 4.25, whereas those with a bachelor’s degree (S1) have a mean of 3.76. Groups based on length of teaching experience obtain mean scores ranging from 3.72 to 3.85. Certified teachers have a mean score of 3.80, while non-certified teachers score 3.75. These findings indicate that teachers demonstrate strong readiness in planning, applying methods, implementing strategies, and evaluating literacy activities at the GLS learning stage.